Power Relations and Women's Strategies in Accessing Property from Unregistered Marriages in Indonesia: A Socio-Legal Analysis - Rohmawati; Muhamad Arifin; Ahmad Gelora Mahardika; Dewi Isna Tsamrotu F (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – The practice of marriages that are not officially registered with a state institution continues to shape contemporary debates on Islamic family law in the Global South, particularly regarding women’s legal status, access to marital property, and inheritance rights. In many Muslim societies, women involved in unregistered marriages face structural barriers in asserting their economic rights, despite the availability of state legal mechanisms intended to provide recognition and protection. Methods - This study employs a socio-legal approach with a gender perspective. Data were collected through in-depth interviews with women who have been or are currently in unregistered marriages, informant observation, and documentation.  Findings - The results of the study indicate that men dominate women in the ownership and management of property, reflecting unequal power relations. In response to these conditions, women have developed two forms of resistance strategies. The public transcript is expressed through confrontational means such as direct demands or legal actions via marriage validation. In contrast, the hidden transcript involves a non-confrontational approach that emphasizes the use of social and familial values. The results of the study demonstrate that women's strategies for accessing property in unregistered marriages are shaped by legal awareness, social dynamics, and local power structures. Limitations - This study emphasizes the female perspective, which can then be explored further through the male perspective in order to obtain a complete picture of the problem of access to property and understanding of male domination. Originality/value - This study fills a gap in the still-limited body of research linking the practice of unregistered marriages to women’s agency strategies rooted in local contexts, while also making a theoretical contribution by enriching the socio-legal perspective on forms of women’s resistance within informal legal structures and power relations.